A review of self‐rated generic quality of life instruments used among older patients receiving home care nursing. (28th March 2017) - Leegaard, Marit; Utne, Inger; Halvorsrud, Liv; Valeberg, Berit Taraldsen; Torbjørnsen, Astrid; Bjørnnes, Ann Kristin; Bjørge, Heidi; Grov, Ellen Karine; Løyland, Borghild
Abstract: In the last two decades, quality of life and health‐related quality of life have become commonly used outcome measures in the large number of studies evaluating healthcare and home care nursing. The objective of this systematic search and review was to evaluate studies that include self‐rated generic quality of life instrument used among elderly patients receiving home care nursing. Searches were conducted in Medline, Embase, PsycINFO and Cinahl for articles published between January 2005 and June 2016, with 17 studies in eight countries meeting the inclusion criteria and assessed for quality. Overall, the review shows great variations in the included studies regarding characteristics of the participants and place of origin, the generic quality of life instruments applied and their dimensions. In this review, we raise the question of whether the generic questionnaires used to measure quality of life do in fact measure what is essential for quality of life in elderly users of home care nursing. The psychological and physical dimensions of quality of life were assessed in almost all included studies, while older‐specific dimensions like autonomy, control and sensation were less frequently assessed. There is reason to believe that generic quality of life instruments frequently do not capture the dimensions that are most important for elderly people with health problems in need of home care nursing.